Description of two new species of scorpions from China (Tibet) belonging to the genera Mesobuthus Vachon (Buthidae) and Heterometrus Ehrenberg (Scorpionidae) - Lourenço, Wilson R.; Qi, Jian-Xin; Zhu, Ming-Sheng (Zootaxa, 2005)
Two new species of scorpions belonging to the genera Mesobuthus (Buthidae) and Heterometrus (Scorpionidae) are described, based on material collected in the region of Pulan, Chinese Tibet (Himalaya). The first, Mesobuthus songi sp. n., is characterized by moderate to large size (with respect to the genus), general coloration reddish-yellow to reddish brown, carinae and granulations strongly marked, and body and pedipalps with very intense setation. The second, Heterometrus tibetanus sp. n. is characterized by moderate size (with respect to the genus), general coloration from reddish-yellow to reddish-brown, pedipalps strongly elongated, and second metasomal segment longer than wide.